Global Emergence and Dissemination of Enterococci as Nosocomial Pathogens: Attack of the Clones? - Guzman Prieto, Ana M.; van Schaik, Willem; Rogers, Malbert R. C.; Coque, Teresa M.; Baquero, Fernando; Corander, Jukka; Willems, Rob J. L. (Frontiers in Microbiology, 2016)
Enterococci are Gram-positive bacteria that are found in plants, soil and as commensals of the gastrointestinal tract of humans, mammals, and insects. Despite their commensal nature, they have also become globally important nosocomial pathogens. Within the genus Enterococcus, Enterococcus faecium and Enterococcus faecalis are clinically most relevant. In this review, we will discuss how E. faecium and E. faecalis have evolved to become a globally disseminated nosocomial pathogen. E. faecium has a defined sub-population that is associated with hospitalized patients and is rarely encountered in community settings. These hospital-associated clones are characterized by the acquisition of adaptive genetic elements, including genes involved in metabolism, biofilm formation and antibiotic resistance. In contrast to E. faecium, clones of E. faecalis isolated from hospitalized patients, including strains causing clinical infections, are not exclusively found in hospitals but are also present in healthy individuals and animals. This observation suggests that the division between commensals and hospital-adapted lineages is less clear for E. faecalis than for E. faecium. In addition, genes that are reported to be associated with virulence of E. faecalis are often not unique to clinical isolates, but are also found in strains that originate from commensal niches. As a reflection of more ancient association of E. faecalis with different hosts, these determinants Thus, they may not represent genuine virulence genes but may act as host-adaptive functions that are useful in a variety of intestinal environments. The scope of the review is to summarize recent trends in the emergence of antibiotic resistance and explore recent developments in the molecular epidemiology, population structure and mechanisms of adaptation of E. faecium and E. faecalis.